Mondo Marcos mga panulat sa batas militar at ng Marcos babies - Cimatu, Frank; Tolentino, Rolando B. (Mandaluyong City Anvil Pub., 2010)
A collection of fiction, essays, and poetry in English by writers who grew up during the martial law period under President Ferdinand Marcos.
Published also as: Mondo Marcos : writings on Martial Law and the Marcos babies.
Keywords: Marcos, Ferdinand E. -- 1917-1989.; Martial law -- Philippines; Philippine literature -- Collections; Philippines -- Politics and government -- 1973-1986.